Ppp2r2a Knockout Mice Reveal That Protein Phosphatase 2A Regulatory Subunit, PP2A-B55α, Is an Essential Regulator of Neuronal and Epidermal Embryonic Development - Panicker, Nikita; Coutman, Melody; Lawlor-O’Neill, Charley; Kahl, Richard G. S.; Roselli, Séverine; Verrills, Nicole M. (Frontiers in Cell and Developmental Biology, 2020)
The serine/threonine protein phosphatase 2A (PP2A) is a master regulator of the complex cellular signaling that occurs during all stages of mammalian development. PP2A is composed of a catalytic, a structural, and regulatory subunit, for which there are multiple isoforms. The association of specific regulatory subunits determines substrate specificity and localization of phosphatase activity, however, the precise role of each regulatory subunit in development is not known. Here we report the generation of the first knockout mouse for the Ppp2r2a gene, encoding the PP2A-B55α regulatory subunit, using CRISPR/Cas9. Heterozygous animals developed and grew as normal, however, homozygous knockout mice were not viable. Analysis of embryos at different developmental stages found a normal Mendelian ratio of Ppp2r2a–/– embryos at embryonic day (E) 10.5 (25%), but reduced Ppp2r2a–/– embryos at E14.5 (18%), and further reduced at E18.5 (10%). No live Ppp2r2a–/– pups were observed at birth. Ppp2r2a–/– embryos were significantly smaller than wild-type or heterozygous littermates and displayed a variety of neural defects such as exencephaly, spina bifida, and cranial vault collapse, as well as syndactyly and severe epidermal defects; all processes driven by growth and differentiation of the ectoderm. Ppp2r2a–/– embryos had incomplete epidermal barrier acquisition, associated with thin, poorly differentiated stratified epithelium with weak attachment to the underlying dermis. The basal keratinocytes in Ppp2r2a–/– embryos were highly disorganized, with reduced immunolabeling of integrins and basement membrane proteins, suggesting impaired focal adhesion and hemidesmosome assembly. The spinous and granular layers were thinner in the Ppp2r2a–/– embryos, with aberrant expression of adherens and tight junction associated proteins. The overlying stratum corneum was either absent or incomplete. Thus PP2A-B55α is an essential regulator of epidermal stratification, and is essential for ectodermal development during embryogenesis.